A High‐Performance Li–Mn–O Li‐rich Cathode Material with Rhombohedral Symmetry via Intralayer Li/Mn Disordering. Issue 16 (4th March 2020) - Song, Jin; Li, Biao; Chen, Yuyang; Zuo, Yuxuan; Ning, Fanghua; Shang, Huaifang; Feng, Guang; Liu, Na; Shen, Chongheng; Ai, Xinping; Xia, Dingguo
Abstract: The search for new high‐performance and low‐cost cathode materials for Li‐ion batteries is a challenging issue in materials research. Commonly used cobalt‐ or nickel‐based cathodes suffer from limited resources and safety problems that greatly restrict their large‐scale application, especially for electric vehicles and large‐scale energy storage. Here, a novel Li–Mn–O Li‐rich cathode material with R 3 ¯ m symmetry is developed via intralayer Li/Mn disordering in the Mn‐layer. Due to the special atomic arrangement and higher R 3 ¯ m symmetry with respect to the C 2 /m symmetry, the oxygen redox activity is modulated and the Li in the Li‐layer is preferentially thermodynamically extracted from the crystal structure instead of Li in the Mn‐layer. The as‐obtained material delivers a reversible capacity of over 300 mAh g −1 at 25 mA g −1 and rate capability of up to 260 mAh g −1 at 250 mA g −1 within 2.0–4.8 V. The excellent performance is attributed to its highly structural reversibility, mitigation of Jahn–Teller distortion, lower bandgap, and faster Li‐ion 2D channels during the lithium‐ion de/intercalation process. This material is not only a promising cathode material candidate but also raises new possibilities for the design of low‐cost and high‐performance cathode materials. Abstract : Intralayer Li/Mn disordering within the Mn‐layer in Li–Mn–O cathode reduces distortion caused by the ionic radius difference and promotes the formation of a structure with R 3 ¯ m symmetry. The unique structure contributes to excellent comprehensive properties: more uniform and less active O states; lower bandgap; a changed delithiation order; and fast Li‐ion mobility. These lead to good stability and rate capability.